Pengaruh Cash Ratio, Debt to Equity Ratio dan Return on Equity terhadap Firm Size dan Deviden Payout Ratio - I Gede Lingga Pramana; Ida Bagus Raka Suardana (Universitas Pendidikan Nasional, 2017)
ABSTRACTThe purpose of this study was to determine the effect of the cash ratio, debt to equity ratio and return on equity on the firm size and devidend payout ratio. This research was conducted in industrial manufacturing company which are listed in the Indonesia Stock Exchange 2013-2015 period. This research is quantitative, which describes causal relationships between variables to analyze numerical data (numbers) using statistical methods through hypothesis testing. The data collection technique using the documentation of 11 companies listed on the Stock Exchange. Data were analyzed using path analysis with AMOS program. The results showed the cash ratio has a positive effect on firm size amounted to 0.358. Debt to equity ratio has a negative effect on firm size amounted to -0.499. Return on equity has a positive effect on firm size amounted to 0.465. Cash ratio has a positive effect on the devidend payout ratio amounted to 0.324. Debt to equity ratio has a positive effect on the devidend payout ratio amounted to 0.232. Return on equity has a positive effect on the devidend payout ratio amounted to 0.717 and firm size has a positive effect on the devidend payout ratio amounted to 0.443.